2017
DOI: 10.3390/fi9030040
|View full text |Cite
|
Sign up to set email alerts
|

Visual Interface Evaluation for Wearables Datasets: Predicting the Subjective Augmented Vision Image QoE and QoS

Abstract: Abstract:As Augmented Reality (AR) applications become commonplace, the determination of a device operator's subjective Quality of Experience (QoE) in addition to objective Quality of Service (QoS) metrics gains importance. Human subject experimentation is common for QoE relationship determinations due to the subjective nature of the QoE. In AR scenarios, the overlay of displayed content with the real world adds to the complexity. We employ Electroencephalography (EEG) measurements as the solution to the inher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
(36 reference statements)
1
13
0
Order By: Relevance
“…This section addresses the general approach to the data generation processes before describing the performance metrics employed in greater detail. Overall, our approach follows that described in prior works, specifically the Visual Interface Evaluation for Wearables (VIEW) datasets [2,[24][25][26]. Our methodology, thus, follows the process illustrated in Figure 1 [2].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This section addresses the general approach to the data generation processes before describing the performance metrics employed in greater detail. Overall, our approach follows that described in prior works, specifically the Visual Interface Evaluation for Wearables (VIEW) datasets [2,[24][25][26]. Our methodology, thus, follows the process illustrated in Figure 1 [2].…”
Section: Methodsmentioning
confidence: 99%
“…Overall, our approach follows that described in prior works, specifically the Visual Interface Evaluation for Wearables (VIEW) datasets [2,[24][25][26]. Our methodology, thus, follows the process illustrated in Figure 1 [2]. A major difference from the prior works is that here, we are not focusing on the generation of reusable datasets, but directly on the evaluation of the gathered data from the new human subject experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that sudden changes of the speed in the translational camera motion and excessive vibration can cause cyber-sickness. Another important recent stream of activities in this direction is the real-time estimation of viewers' QoE levels exploiting physiological signals [20], [21], [22]. This category of activities aims at tracking singular or combinations of physiological responses (e.g., heart rate, electro-dermal activity, and electroencephalogram) in the course of immersive media experience.…”
Section: Challenges With Interactivity and Quality Of Experiencementioning
confidence: 99%